REFLEKSI SOSIAL MASYARAKAT PADA REZIM ORDE BARU DALAM NOVEL LAUT BERCERITA KARYA LEILA S. CHUDORI: KAJIAN SOSIOLOGI SASTRA IAN WATT - Akhyar, Andi Imamul; Nensilianti, Nensilianti; Mahmudah, Mahmudah (Fakultas Bahasa dan Sastra Indoensia, 2025)
This research aims to reflect the ife of society in the new order regime contamined in the novel Laut Bercerita by Leila S. Chudori using Ian Watt sociology of literature study. The focus is on te social context of the author’s reflection of the society in the novel Laut Bercerita using a qualitative descriptive method and literary text analysis. The result show that there are 8 forms of social reflectionin the novel Laut Bercerita which contains discrimination, intimidation, repression, authoritarian, injustice fear, and anxiety of the community some of these social reality phenomena are perfectly poured into the novel’s work of fiction.